Applying Exit Survey Analysis in Ensuring the Improving Quality Of Academic Quality - Luki Yunita (Universitas Sembilanbelas November Kolaka, 2017)
Problems that become the study of this research is Exit Survey Analysis In Ensuring Quality Improvement of Academic Quality. This study aims to analyze the exit survey developed at UIN Syarif Hidayatullah Jakarta as part of the monitoring and evaluation efforts obtained from graduation students. Monitoring and evaluation conducted in this survey exit, thesis supervision, and academic advisor. Analysis was done by considering four aspects of content, administration, analysis, and integration strategy. This research was conducted at UIN Syarif Hidayatullah Jakarta. The research was conducted from March to August 2016 at UIN Syarif Hidayatullah with respondents of the graduates from various faculties and study programs. The result of this research was: 1) Based on the content it can be seen that items in service survey, thesis supervision and academic advisor have medium reliability. This provides an opportunity for institutions to review the items that have not been done thoroughly and comprehensively, 2) Based on this online administration has several advantages such as the effectiveness of time, human resources and budget. Nevertheless, the potential weaknesses of the online system also need to be considered among them is the stability of the network and the system itself, 3) To provide a reading of data analysis results that are beneficial for service improvement, the exit survey data is analyzed using Rasch Model. It provides detailed analysis of items and respondents and mentors / advisers in detail, 4) integration strategies have great potential to have a significant impact on quality development efforts. Nevertheless, in this study the integration strategy cannot be done considering the need for further steps such as the publication of results to the leadership, the leadership commitment to the recommendations, as well as monitoring and evaluation of leadership commitments within the agreed timeframe.